The influence of CPC reflectors on the electrical incidence angle modifier of c-Si cells in a PVT hybrid collector. (March 2016) - Proell, M.; Karrer, H.; Brabec, C.J.; Hauer, A.
Graphical abstract: Highlights: An experimental CPC PVT solar collector was built, in order to examine the impact of CPC reflectors on the pv efficiency. Ray tracing simulations showed the flux distribution of CPC reflectors for different incoming angles. Eight different CPC geometries with three different concentrations were built and tested under in situ conditions. A model combined ray tracing, thermal and electrical behavior and quantified the various effects of pv efficiency loss. Abstract: PVT collectors aim for the co-generation of pv electricity and heat. The following concept intents to raise the thermal efficiency by concentrating sunlight with CPC reflectors, in order to access a higher number of solar thermal applications. The work presented here, focuses on the influence of the CPC reflectors on the pv efficiency. Parabolic concentrators in general, and CPC reflectors in particular, cause a non-uniform illumination of the pv cells, which decreases the pv efficiency. Ray tracing calculations of one particular CPC geometry result in a characteristic, angular dependent solar flux distribution in the cell plane. The effect of this flux distribution was measured on a real scale experimental collector on a outdoor solar test stand. The incidence angle modifier (IAM) of the pv efficiency was measured for three different concentrations, as well as for an improved CPC geometry, aiming to homogenize the flux distribution in the cell plane. The experiments showed, that the pv efficiency drops from 15% at STC to between 9% and 11%, depending on the solar concentration factor, which influences the efficiency negatively. The predicted efficiency boost of the improved CPC geometry could not be validated experimentally, as the additional optical losses of the more complex setup were high compared to its improvement effect. In order to understand these results, a theoretical model was built, combining ray tracing, electrical and thermal modeling of the CPC PVT collector. This model enabled to calculate the temperature distribution, as well as the pv efficiency simultaneously, by dividing the pvt absorber into finite elements.